Kinetics and Mechanism of the Oxidation of Substituted Benzyl Alcohols by Pyrazinium Dichromate - DEGIRMENBASI, NEBAHAT; BOZ, NEZAHAT (Asian Journal of Chemistry, 2010)
Pyrazinium dichromate oxidizes benzyl alcohol and substituted benzyl alcohols to the corresponding aldehydes in dimethyl sulfoxide and in the presence of acid. The rate of the reaction is dependent on the concentrations of the substrate, pyrazinium dichromate and acid. The oxidation of α,α-dideuteriobenzyl alcohol exhibits a substantial primary kinetic isotope effect (kH/kD = 6.61 at 303 K). Polymerization of acrylonitrile is not induced in this reaction. From the kinetic data, the activation parameters have been calculated. The analysis of the dependence of the kinetic isotope effect on temperature indicated that the reaction involves a symmetrical cyclic chromate ester in the rate-determining step. A suitable mechanism has been proposed.